Apoptotic potential of two Caryophyllaceae species in MCF-7 and MDA-MB-468 cell lines - M. Mosaddegh; M. Taheri; B. Eslami Tehrani; M. Hamzeloo-Moghadam* (Iranian Society of Pharmacognosy, 2018)
Background and objectives: Plants have been used to treat diseases like cancer for many years and today the trend towards their use is increasing. One of the most effective mechanisms of plants against cancer is inducing apoptosis. Apoptosis is a programmed cell death which acts opposite to cell division. It starts in response to some stimuli. Despite the effectiveness of apoptosis inducing agents, their use has been limited due to side effects and resistance to these treatments; so, applying medicinal herbs due to their lower cost and toxicity has drawn attentions. Recent research at the Traditional Medicine and Materia Medica Research Center, Shahid Beheshti University of Medical Sciences on two medicinal plants Acanthophyllum bracteatum and A. microcephalum has shown cytotoxic effects of these two species, but the mechanism of their toxicity has remained unknown; thus, the present study was designed to evaluate the apoptotic potential of Acanthophyllum bracteatum and A. microcephalum. Methods: In the present study, the cytotoxic effects of the methanol extract of Acanthophyllum bracteatum and A. microcephalum was evaluated against MCF-7 and MDA-MB-468 cells by MTT assay; furthermore, their apoptosis potential has been evaluated by annexin-V/propidium iodide assay and Hoechst 33258 staining in the same cell lines. Results: The methanol extract of A. microcephalum and A. bracteatum showed cytotoxic effects against MCF-7 and MDA-MB-468 cell lines with IC50 values of 64, 159 and 102, 250 μg/mL, respectively. The results of the apoptosis assays confirmed the potential of the two plants extracts to induce apoptosis in both cell lines while A. microcephalum demonstrated more considerable results. Conclusion: A. microcephalum could be a suitable choice for further breast cancer studies.